Numerical Simulation of Global Temperature Change during the 20th Century with the IAP／LASG GOALS Model - 马晓燕 郭裕福 石广玉 俞永强 (Advances in atmospheric sciences, 2004)
The IAP/LASG GOALS coupled model is used to simulate the climate change during the 20th centuryusing historical greenhouse gases concentrations, the mass mixing ratio of sulfate aerosols simulated by aCTM model, and reconstruction of solar variability spanning the period 1900 to 1997. Four simulations,including a control simulation and three forcing simulations, are conducted. Comparison with the observa-tional record for the period indicates that the three forcing experiments simulate reasonable temporal andspatial distributions of the temperature change. The global warming during the 20th century is causedmainly by increasing greenhouse gas concentration especially since the late 1980s: sulfate aerosols offseta portion of the global warming and the reduction of global temperature is up to about 0.11°C over thecentury; additionally, the effect of solar variability is not negligible in the simulation of climate changeover the 20th century.